(untitled) (Economic studies journal, 2021)
Abstract This study aims to reveal the reality of academic research in the Libyan Academy from the point of view of graduate students at the School of Administrative and Financial Sciences in the city of Misurata. To achieve this aim, the descriptive approach was utilized. The study population consisted of graduate students at the School of Financial Administrative Sciences (Management and Organization Department and Business Administration Department). Their number was (114). The study adopted a questionnaire as a main tool for collecting data from the study sample, which consisted of (39) respondents, equivalent to 34% of the whole population. To analyze the data collected from respondents, a computer was used and the Statistical Package for Social Sciences (SPSS) program version 20 was used. Based on the analysis of quantitative data, the study reached a set of results, most notably: the convergence of the answers of respondents about the reality of academic research at the Libyan Academy of Misurata from the point of view of graduate students. They were all with a weighted average between medium and high importance. The results show that the most important dimensions - among dimensions of the reality of academic research - are the dimensions of academic research procedures and their results; research and development environment; organization; quality of student research; and funding of academic research. The results of the Spearman analysis test shows that there is a positive correlation between the dimensions of reality of academic research. The results show that there are statistically significant differences for the opinions of respondents about reality of academic research due to the variable of age. While there are no statistically significant, differences for the opinions of respondents to the reality of academic research that are attribu the variables of gender, marital status, and the field of interest in the Libyan Academy, Misurata branch. The study recommended the following: Providing researchers with requirements and appropriate environment and sufficient capabilities of equipment and laboratories. Developing the current databases to serve academic research. Encouraging graduate students to conduct academic research and publish outstanding ones in academic journals locally and abroad. Increasing the budgets allocated to academic research in line with or exceed global rates of gross national product. Holding training courses and organizing study workshops and discussion seminars on a regular and continuous basis, in the field of preparing academic research for the benefit and interest of graduate students and teaching staff members.